Dental evolution in Neophanomys (Rodentia, Octodontidae) from the late Miocene of central Argentina - Verzi, Diego Hector (2011)
The evolutionary pattern of the molar morphology of the small caviomorph (Octodontidae) Neophanomys from the late Miocene Cerro AzulFormation of central Argentina is analyzed. Two new species (chronomorphs) are recognized, which constitute an anagenetically evolving lineagewith a gradual and directional pattern of increasing molar hypsodonty. Dental changes related to increasing hypsodonty are comparable to those ofthe octodontid lineage Chasichimys also recovered from the Cerro Azul Formation. However, Neophanomys shows comparatively less variation ingross morphology and there are no evidences that this lineage achieved euhypsodonty. In contrast, important changes in enamel microstructure(schmelzmuster) are observed among different populations of Neophanomys, supporting the hypothesis that these changes can occur at leastpartially independently from modifications in dental gross morphology. The patterns of dental evolution detected in the Neophanomys andChasichimys-Xenodontomys lineages and the unequivocal polarity of the changes involved, related to increasing hypsodonty, reinforce thehypothesis that chronological differences exist among late Miocene outcroppings of Cerro Azul Formation in central Argentina.